2021
DOI: 10.1108/jeim-02-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fluctuations of environmental regulation, technological innovation, and economic growth: a multinational perspective

Abstract: PurposeEnvironmental regulation is in a continuous state of intense change and modification amid the long-term tensions between environmental protection and economic growth. In this article, the authors creatively investigate how fluctuations of environmental regulation influence a nation's economic growth while also examining the mediating effect of technological innovation.Design/methodology/approachUsing sample data of 36 Organisation for Economic Co-operation and Development (OECD) countries from 2013 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Ideally, innovation has been perceived as a tool for bringing environmental benefits. The studies by Anthony et al (2018) and Xie et al (2021) indicate the environmental benefits of innovation. However, the recent work by Chen et al (2021) indicates the negative social externalities exerted by innovation.…”
Section: Implications For Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, innovation has been perceived as a tool for bringing environmental benefits. The studies by Anthony et al (2018) and Xie et al (2021) indicate the environmental benefits of innovation. However, the recent work by Chen et al (2021) indicates the negative social externalities exerted by innovation.…”
Section: Implications For Theorymentioning
confidence: 99%
“…The studies by Anthony et al. (2018) and Xie et al. (2021) indicate the environmental benefits of innovation.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Shen et al (2019) studied the nonlinear dynamic effects of various categories of ER on environmental total factor productivity (ETFP) in the industrial sector using a threshold model and found that a high strength of environmental regulations undermines technological innovation in these firms. Xie et al (2021) explored the impact of ER fluctuations on a country's economic growth, and the research results showed that both formal ER fluctuations and informal ER fluctuations had significant negative impacts on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Times series and regression methods are other topics that we published some high-quality papers (Miao, 2021; Xie et al , 2021; Yang et al , 2021a; Yaoteng and Xin, 2021; Duan et al , 2022). For example, Zhao and Chen (2021) examined the role of an effective government and an effective market in preventing and controlling the withdrawal of innovators.…”
Section: Article Classificationsmentioning
confidence: 99%